The concept of "ideology" in Nietzsche's philosophy : the construction of the subject - Mutlu, Erol. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
Although Nietzsche employs the concept of “ideology” very rarely, his strong critique of Western culture can be read, in terms of methodology and content, as an analysis of ideology. The values, ideals, idols, illusions, delusions, images and representations he attacks are the constitutive elements of the corpus of an ideology. Ideology works as a “reality” in Nietzsche’s writings. This thesis aims to reveal the results and hints Nietzsche’s analyses might suggest concerning the “theory of ideology” which was a topic of lively debate in the 1970s. The category of the subject, the constitutive element of ideology, plays a permanent and decisive role in Nietzsche’s analyses. Any interpretation and evaluation that aims to give meaning to and organize life conceals its own partial and perspectival character, becomes totalitarian as it claims to be universal and eternal, and builds its own regime. The subject is constructed as a controversial and vulnerable fiction in the context of this power struggle. Nietzsche’s aim is to break into pieces the decadent structure that has turned into nihilism, and create a new world of values, a conception that will liberate the self. The problem emerges exactly at this point of conceptualization of the agents that is, the “free spirits” who will carry out this strategic undertaking. A philosophy which posits that the subject depends on a perfect automatism of instinct, that human activity is possible only through a suspension of thinking and pushing the real conditions of existence into the unconscious, will have difficulties in explaining the conditions under which the “free spirits” will create a new world of values. The tension in Nietzsche’s philosophy stems from the fact that the project it undertakes is engaged in an enormous problematic that goes beyond the limits of human activity: The recreation of the self and the world. Yet the conditions which will render possible this self-creation are challenged by the most essential claims of its analysis. On a stage where the society is identified with the “herd” and the relation of mutual recognition in the intersubjective sphere is destroyed, the freespirited individual of the future will either create himself with a godlike, isolated and hermitic action, or will be destroyed, losing his self and spiritual integrity. Thus the subject is a hold for the practice of ideology and in turn, it is under its attack..